Enhancing oxidation resistance of Cu(I) by tailoring microenvironment in zeolites for efficient adsorptive desulfurization - Yu-Xia Li (Nature Portfolio, 2020)
Zeolite Cu(I)Y is attractive for adsorptive removal of sulfur compounds from fuel, however practical application is limited by instability of Cu(I). Here the authors use a coating to achieve superhydrophobicity in the zeolite, leading to improved Cu(I) stability against oxidation and thiophene removal.